2015
DOI: 10.1149/06906.0003ecst
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Dicing: Current State & Future Trends

Abstract: Die singulation by mechanical sawing has been the primary technology used in semiconductor device fabrication for decades. However, as device structures continue to evolve to meet increasing performance requirements, fundamental limitations of the sawing operation have been exposed. Obtaining reasonable dicing throughput and yield for die less than 100µm thick is a challenge for the sawing operation. One alternative to saw-based dicing is die singulation using plasma etching. This paper compares and contrasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Westerman et al have revealed that the die fabricated through plasma dicing had nine times higher die strength than dies that were cut mechanically [84]. In addition, 29,251 dies of 1 mm 2 size were obtained from 200 mm diameter wafers using plasma dicing, showing a more efficient method than mechanical dicing (24,867 dies) and laser dicing (26,798 dies).…”
Section: Plasma Dicing Of Si-wafer With Tsvsmentioning
confidence: 99%
See 1 more Smart Citation
“…Westerman et al have revealed that the die fabricated through plasma dicing had nine times higher die strength than dies that were cut mechanically [84]. In addition, 29,251 dies of 1 mm 2 size were obtained from 200 mm diameter wafers using plasma dicing, showing a more efficient method than mechanical dicing (24,867 dies) and laser dicing (26,798 dies).…”
Section: Plasma Dicing Of Si-wafer With Tsvsmentioning
confidence: 99%
“…They also showed how the process and sidewall quality for plasma dicing affected the die break strength at various orientations and presented a comparison of sidewall quality and process timings to traditional mechanical blade dicing for certain die sizes. Westerman et al have revealed that the die fabricated through plasma dicing nine times higher die strength than dies that were cut mechanically [84]. In add 29,251 dies of 1 mm 2 size were obtained from 200 mm diameter wafers using plasm ing, showing a more efficient method than mechanical dicing (24,867 dies) and laser d (26,798 dies).…”
Section: Plasma Dicing Of Si-wafer With Tsvsmentioning
confidence: 99%
“…We estimated that currently our FET failure would cause a 1 % inconsistency, but this can be reduced to a very low level in a mature device fabrication process. To safely separate twin PUFs, the distance between twin PUFs must be larger than approximately 30 μm, considering that the cut size is approximately 10 μm using plasma dicing 51 . According to the simulated results, the consistency of twin PUFs will decrease to a barely acceptable value of 85 % when the PUF distance is 30 μm (Fig.…”
Section: Consistency Of Twin Pufs and Secure Communicationmentioning
confidence: 99%